"Relación entre perfeccionismo y estrés en los adolescentes de la Institución Educativa Alexander Graham Bell - Trujillo, 2009" - Huertas Salvatierra, Neuza Marilia de la Trinidad (2009)
This research study is a quantitative, descriptive and correlational cross. It was performed in adolescents in the school-Alexander Graham Bell between February and June 2009 with the purpose of determining whether a relationship exists between the type of perfectionism and the type of stress in adolescents. The sample consisted of 144 adolescents who met the inclusion criteria set. The information was obtained through the Multidimensional Perfectionism Scale and physical and psycho-emotional stress Scale, which were valid and reliable. The results were tabulated and presented in simple tables, double entry tables and graphs. The statistical analysis was performed for test the independence of criterion, Chi-square test (x2). The conclusion of the analysis was: the highest percentage of adolescents showed a negative kind of stress (83 percent) and an unhealthy perfectionism (90 percent) also showed that not exist the relationship was significant (P <0.05) between type Perfectionism and type of stress in adolescents.